Effect of Pomegranate Extract and Chlorhexidine Mouth Wash on Post-Operative Complications After Surgical Removal of Wisdom Teeth - Haider Ali Rassul; Ahmad Fliah Hassan; Hani Radhi; Jabber J. Kareem (College of Pharmacy / Mustansiriyah University, 2018)
The purpose of this study is to evaluate the effectiveness of pomegranate mouth wash in comparison with chlorhexidine mouth wash on post-operative complications result from surgical removal of wisdom teeth.             Forty Iraqi patients who underwent surgical removal of impacted wisdom teeth were divided into two equal groups, patients in first group were instructed to use pomegranate mouth wash while those in the second group used chlorhexidine mouth wash. Post operative complications as pain, swelling, trismus and oozing were examinated for both groups at second, fourth and seven days after operation. The data were statistically analyzes and compared between the groups.             A significant difference was shown between the two groups of pomegranate and chlorhexidine mouth wash according to each parameters (first = pain, second= swelling, third= trismus, forth= oozing) depends on the days of post-surgical assessment (second days, forth days and seven days).             In Conclusions the effectiveness of pomegranated mouth wash was better than chlorhexidine mouth wash on post operative complications following the surgical removal of third molars (wisdom).